Influence of socio-demographic characteristics in the self-care of people with heart failure - Cavalcante,Luiza Marques (2018)
ABSTRACT Objective: To determine the influence of socio-demographic characteristics in the self-care of people with heart failure (HF). Method: Cross-sectional, analytical study, held in three private hospitals in Fortaleza, Ceará, Brasil, with 57 hospitalized patients. The data were collected through a demographic characterization form and a self-care assessment scale and were analyzed with inferential statistics, using mean comparison tests. Results: Self-care was best assessed in people with higher education level, higher household income and in a relationship. Conclusion: The socio-demographic characteristics influenced seven self-care practices: dietary control; monitoring of body weight; effort in labor activities; knowledge about HF; up-to-date vaccination record; leisure activities; and family and social support network with strong bonds. The higher prevalence of answers indicating satisfactory self-care practices among the patients occurred in the areas of health promotion and tolerance to stress.